Ways of implementation of the national concept of the integrated organization of police activity - Solntseva, Khrystyna (Problems of legality, 2021)
The analysis of the current law enforcement system allows to state the existence of certain problems related to its construction and some aspects of activity. After the administrative reforms in Ukraine, the indicators of assessing the level of public confidence in the National Police gradually began to improve, but the practice of foreign countries shows better breakthroughs in the organization of policing. Therefore, the relevance of the article is explained by the need to introduce in the national legal system a new concept of policing, which would take into account the successful experience of foreign countries and course of our country for European integration. First of all, the article is devoted to the analysis of the existing models of law enforcement systems in the world in order to determine the most favorable and effective for national law. It was found that the integrative model of organization of police activities today demonstrates the most effective indicators in the work of foreign police, so it can be considered a guide for implementation in Ukraine. Based on this, the author proposes his own definition of the term "integrated policing". The author pays special attention to the successful experience of the Baltic States and the United States in policing, in particular in the field of training highly qualified police officers, police and community cooperation in partnership, and international cooperation in exchanging experience of specialized law enforcement services. For example, the national legal system should pay attention to such development programs as the creation of port police, increasing the duration of specialized training of police officers, involving citizens in patrols on a voluntary basis, increasing the competence of local police departments. Analyzing the relevant practice of foreign countries, the author pays attention to the peculiarities of the functioning of the national law enforcement system, as well as its own achievements. In conclusion, there are several possible ways to introduce into the legislation of Ukraine the main development programs and principles of functioning of the police of foreign countries in Europe and America. The main result of the work is the design of the concept of an integrated organization of policing and the expected results from its implementation - reaching a new level in the process of European integration.